Investing in their future Cambodia's children - Griffiths, Steven; Information Office Asian Development Bank. (Manila Asian Development Bank, 1996)
Cambodia had to start from scratch after two decades of war and devastation. In the education sector the problems were immense: an acute shortage of teachers since many has had been killed under the Khmer Rouge regime, inadequate classrooms, antiquated curriculum and a dearth of teaching materials. With the help of the international community, Cambodia id rebuilding from the bottom up, targeting the primary school in an effort to increase literacy and reduce the drop-out rate.
3With 3 converted disc.
Scriptwriter, Ian Gill ; Narrator, Robert Salamon ; Online editor, Roberto Regalado.
VHS.
In Khmer, with English subtitle.
Keywords: Cambodia -- Social conditions